1984
DOI: 10.1016/0014-5793(84)80820-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of analogues of adenosine and methyl xanthines on insulin sensitivity in soleus muscle of the rat

Abstract: The concentration of insulin that produces half‐maximal stimulation of glycolysis by stripped soleus muscle preparations is markedly increased by the adenosine analogues, 2‐chloroadenosine and N 6‐phenylisopropyladenosine, but is markedly decreased by the methyl xanthine analogue, 8‐phenyltheophylline. 2‐Chloroadenosine increases the concentration of insulin required to stimulate glycolysis half maximally, from about 100 to 2000 μunits/ml. 8‐Phenyltheophylline decreases this concentration of insulin from about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…Our results showing that activation of the A 1 adenosine receptor increases while A 1 adenosine receptor antagonism is without effect on insulin-stimulated glucose transport is congruent with Han et al (1998), but not with Budohoski et al (1984), Challiss et al (1992), Espinal et al (1983), or Hashimoto et al (1987. Similarly, our results showing that adenosine modulation of glucose transport facilitated by insulin contributes to insulin sensitivity but not to responsiveness are also compatible with most (Challiss et al 1992; Fig.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Our results showing that activation of the A 1 adenosine receptor increases while A 1 adenosine receptor antagonism is without effect on insulin-stimulated glucose transport is congruent with Han et al (1998), but not with Budohoski et al (1984), Challiss et al (1992), Espinal et al (1983), or Hashimoto et al (1987. Similarly, our results showing that adenosine modulation of glucose transport facilitated by insulin contributes to insulin sensitivity but not to responsiveness are also compatible with most (Challiss et al 1992; Fig.…”
Section: Discussionsupporting
confidence: 42%
“…Dagger ({) indicates p < 0.05 vs. insulin alone. Budohoski et al 1984;Heseltine et al 1995;Kuroda et al 1987), but not all (Han et al 1998), studies. One possibility for these discrepancies might be related to the concentrations of insulin and (or) the pharmacological agents employed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Insulin activation in muscle tissue is not only associated with inhibition of glycolysis but with transport of glucose and activation of glycogen synthesis. Reports show that adenosine had an effect on only glycolysis (Espinal et al, 1983; Budohoski et al, 1984; Challis et al, 1984) and glucose transport by stimulation of the insulin sensitive glucose transporters GLUT4 (Vannucci et al, 1992); glycogen synthesis was not affected by adenosine (Challis et al, 1984). In isolated soleus muscles from rats, it was found that depletion of adenosine (by adenosine deaminase) in the surrounding media improved insulin sensitivity.…”
Section: Adenosine and A1 Adenosine Receptorsmentioning
confidence: 99%
“…The observed effect on insulin sensitivity was due to decrease in the concentration of insulin necessary to activate glycolysis (Espinal et al, 1983). Using the same model and adenosine analogs, reduction in insulin sensitivity was observed when insulin levels were reduced to half of the maximum dose required to stimulate glycolysis in the muscle (Budohoski et al, 1984). Non‐specific adenosine receptor antagonists (methyl xanthines) reversed the inhibitory effect of adenosine on insulin signaling (Budohoski et al, 1984).…”
Section: Adenosine and A1 Adenosine Receptorsmentioning
confidence: 99%